(untitled) (Research, Society and Development, 2022)
Mikania hirsutíssima (family), commonly known in Brazil by the name of "cipó-cabeludo", is widely used in folk medicine. The antimicrobial activities have already been investigated, however, no studies have been carried out to evaluate the plant’s antifungal activities. Therefore, the objective of this work was to evaluate the antifungal activity of Mikania cf hirsutissima extract in clinical isolates and standard strains of Candida albicans resistant to fluconazole and itraconazole. After the collection of Mikania cf hirsutissima, it was dried, crushed and weighed, leaving the material on waste in absolute alcohol. After the rest, the crude extract of the stem and leaf was obtained. Clinical isolates of Candida albicans and standard strains were used. Different ethanolic concentrations of leaves and stems were used. To determine the in vitro antioxidant activity of the ethanol extract, the DPPH free radical method was applied. The antifungal activity of ethanolic extracts in Candida albicans strains showed satisfactory results, where the 100 mg/mL stem extract showed average halos of 4.5 mm. All strains were resistant to the antifungals itraconazole and fluconazole. The extract concentrations tested for the evaluation of antioxidant activity showed antioxidant capacity compared to the standard of BHA. The results showed antifungal activity in Candida albicans isolates, where all parts showed fungicidal potential, even in those resistant to Fluconazole and Itraconazole. Thus, the positioning of these compounds in clinical practice may contribute to expand the possibilities of treating infections caused by this species of yeast.